A Work study on Golden Cane Furniture Manufacturing Corporation - Ansaldo, Ma. Lalaine (College of Engineering, 1992)
The project study has 3 major areas of concern. These are Methods Study, Work Measurement, and Systems and Procedures. These areas have been studied closely and the group has come up with several recommendations. Perhaps due to the fact that Golden Cane Furniture Manufacturing Corporation is relatively new (since 1967), the group has noted several improvements needed concerning mainly its plant layout and working conditions.